On the value of restrictive covenants: Empirical investigation of public bond issues - Reisel, Natalia (Journal of Corporate Finance, 2014)
Are restrictive covenants effective mechanisms in mitigating agency problems? Is the magnitude of the increase in the cost of debt due to agency problems non-trivial? We tackle these questions using a large dataset of public bonds. Contrary to the view that restrictive covenants in public bond contracts are standard boilerplates that serve little purpose, we find significant benefits in terms of reduction in the cost of debt associated with covenants. Restrictions on investment activities or issuance of higher priority claims reduce the cost of debt by about 35–75 basis points. These findings suggest that investors view bond covenants as important instruments in mitigating agency problems, and an increase in the cost of debt due to agency problems could be substantial. Additionally, we find that high growth firms and firms with low probability of default are less likely to include covenants suggesting that the costs of covenants outweigh benefits for these types of firms.